The roles, responsibilities and perceptions of community health workers and ward-based primary health care outreach teams: a scoping review - Euphemia Mbali Mhlongo; Elizabeth Lutge; Lateef Adepeju (Taylor & Francis Group, 2020)
Background Community health workers play important roles in rural primary health care settings. They work within ward-based primary health care outreach teams yet their roles are not always clearly defined and operationalized. There is thus a need to explore perceptions about the roles and responsibilities of community health workers. Objective To investigate the roles, responsibilities and effectiveness of community health workers working within ward-based primary health care outreach teams. Method A scoping review of the published peer reviewed literature on community health workers working in ward-based primary health care outreach teams within low and middle-income countries was conducted. The following five electronic databases were searched: EBSCOhost, Google Scholar, Science Direct, EMBASE, PubMed, and Clinical key. Out of 69,969 identified articles, 31 met the inclusion criteria. The majority of the studies were from South Africa. Results Both positive and negative perceptions were reported. Suggestions for improvements were also put forward. Positive factors included: ongoing training and up skilling; collaboration and trust building with other health care workers; mentoring and supervision; motivation and recognition, and incentives and remuneration. Negative factors covered: inadequate mentorship and poor supervision; role conflict; lack of support; poor remuneration; inadequate manpower; poor knowledge, and insufficient training. The review identified the following as the roles and responsibilities of community health workers: conducting home visits; identifying vulnerable community groups; promoting health and wellness; increasing access to health care; contact tracing; delivering health education; giving counselling and psychosocial support, and providing preventive health services. Conclusion The information available for community health workers in terms of their roles, responsibilities and effectiveness is inadequate, considering their roles and responsibilities in ward-based primary health care outreach teams. This lack of information constitutes barriers to effective service delivery, a common situation among this group of community health workers.